Efektivitas Amandemen Organik dan Trikoderma dalam Meningkatkan Kualitasi Pembibitan Kopi Arabika pada Tanah Andisol Kecamatan Namanteran Kabupaten Karo - Diki wahyudi Hutabarat; Andi Setiawan; Kabul Warsito (Universitas Teuku Umar, 2025)
This research aims to evaluate how effective the use of organic amendments and Trichoderma mushrooms is in increasing the quality of Arabica coffee seeds planted on Andisol type land in the Namanteran District, Karo Regency. The method used is a random igroup design (RAK) with a single treatment design (non-factorial), which consists of eight different treatments and each of them is repeated four times. The treatments include: A0 (no treatment/control), A1 (compost 20 g + Trichoderma 10 g per plant), A2 (biochar 20 g + Trichoderma 10 g per plant), A3 (manure 20 g + Trichoderma 10 g per plant), A4 (manure 20 g + biochar 20 g + Trichoderma 10 g per plant), A5 (compost 20 g + biochar 20 g + Trichoderma 10 g per plant), A6 (compost 20 g + 20 g + Trichoderma 10 g per plant), and A7 (biochar 20 g + manure 20 g + Trichoderma 10 g per plant). The parameters observed in this research include plant height, stem diameter, leaf number, leaf surface area, and root system length. This treatment showed a real influence on all plant growth parameters, including height, stem diameter, number of leaves, leaf area, and root length at ages 2 and 3 BST.Keywords: Coffee, Seedling Cultivation, Organic Amendment, Trichoderma